New positive patch test reactions on day 7: the additional value of the day 7 patch test reading - Amerongen, Cynthia C. A. van; Ofenloch, Robert (Contact dermatitis, 2019)
Background Not performing a day (D) 7 patch test reading might result in positive patch test reactions being missed. Objectives To investigate the added value of the D7 patch test reading for individual allergens, and to identify patient characteristics and allergen groups associated with new positive D7 reactions. Methods Data from patients patch tested between 2008 and 2018 with the extended European baseline series were analysed. Patch test readings were performed on D3 and D7. Positive reactions were categorized into positive on D3 or new positive on D7. Results A total of 3292 patients were consecutively patch tested with at least 43 allergens of the TRUE Test panels 1 and 2 supplemented with investigator-loaded allergens. In total, 447 (13.6%) patients showed new positive D7 reactions. In univariable regression analysis, age between 18 and 30 years showed a negative association with new positive D7 reactions. Significantly more D7 positive reactions were seen for topicals (odds ratio [OR] 2.60, 95% confidence interval [CI]: 1.92-3.51) and corticosteroids (OR 1.87, 95%CI: 1.09-3.21). No associations were found between sex, atopic dermatitis and occupational dermatitis and a new positive D7 reaction. Conclusion A D7 reading to identify new positive patch test reactions is of added value, especially for topicals and corticosteroids.